2019
DOI: 10.5647/jsoee.28.4_21
|View full text |Cite
|
Sign up to set email alerts
|

Nature-based early childhood activities as environmental education?: A review of Japanese and Australian perspectives

Abstract: In this paper we review the forest kindergartens and Skogsmulle programs (Swedish outdoor programs) as well as the formally registered early childhood services in Japan. All of these different service types are known to include nature-based activities for young children. The formally registered early childhood services are subject to national guidelines (CAO et al. 2017, MEXT 2017, MHLW 2017) that require nature-based activities to promote children's development. However, these guidelines fall short on matters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Indeed, a large research project on sustainability conducted within the World Organization for Early Childhood Education (OMEP) during 2009-2014 showed that adults tend to underestimate the competencies of young children [16]. Even in Japan, there is a lack of views of children as having agency according to the national curriculum and the teacher's handbook of environmental education [17]. However, the images of young children have changed and they are viewed as capable and competent learners with an active role in their own learning and the learning of others [18][19][20].…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
“…Indeed, a large research project on sustainability conducted within the World Organization for Early Childhood Education (OMEP) during 2009-2014 showed that adults tend to underestimate the competencies of young children [16]. Even in Japan, there is a lack of views of children as having agency according to the national curriculum and the teacher's handbook of environmental education [17]. However, the images of young children have changed and they are viewed as capable and competent learners with an active role in their own learning and the learning of others [18][19][20].…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
“…The paper confirms that when educators take the time to focus on the environmental learning and understand that environmental education is more than just learning through play (Davis, 2010), they can extend the children’s play and scaffold to support the children’s learning. As indicated earlier, the language of environmental education is understood differently by individuals, organisations and various groups (Inoue et al, 2019). Using a specific definition, the five components from EPA America provide opportunities to link in with specific behaviours and understandings and are beneficial in analysing the data provided in the vignettes.…”
Section: Discussion: Bush Kinder Benefits Building An Affinity With N...mentioning
confidence: 99%
“…For example, they may start to understand the importance of the sun, air, soil and water (Campbell & Speldewinde, 2019). Inoue, Elliott, Mitsuhashi, and Kido (2019) highlight that young children will experience the cycles of life through observing living things and will consider different species' diversity and habitats and possibly how these interact with each other. They will notice change over time, as the seasons evolve, and the environment responds to the changing conditions.…”
Section: Bush Kinders and The Educator's Role In Fostering Environmen...mentioning
confidence: 99%
“…However, there can be large differences among outdoor learning models and outcomes. Inoue et al (2019) found, for example, that Japan's national guidelines on nature-based activities to promote child development "fall short on matters of global sustainability, environmental issues, environmental education, or education for sustainability". Inoue et al (2019) also noted that there were limitations to the Australian guidelines in these areas and concluded that 'forest kindergartens' and Swedish skogsmulle 2 outdoor programmes offer more potential.…”
Section: Asia and The Pacific (Ap)mentioning
confidence: 99%